Rise and fall / 6. - Schrefer, Eliot, 1978- (Spirit animals, 2015)
Conor, Abeke, Meilin, Rollan and their spirit animals have been scattered on their quest for the talismans and must make their way into the desert kingdom of animals ruled by Cabaro, the Great Lion, to retrieve the golden talisman he guards.